Spanish elections, 1936 : inter-departmental correspondence - White, N. I.
015b_0039_001 TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From N.I. White To Sir Walter Citrine Department Research Date 1st. December, 1936. SUBJECT. SPANISH ELECTIONS, 1936. The following facts with regard to the last Spanish elections are given in Edward Conze's "Spain To-day", which was published a few months ago by Secker and Warburg:- Votes Seats Popular Front 4,356,000 162 Left Republicans 108 Socialists and Communists * Centre 340,000 60 Right 4,570,000 140 * The number of Communists was 16. This estimate of the voting has been confirmed from another source, and the total number of seats (470) from a third. The "Times" of Feb. 27th, 1936, gives more detailed information as to the constitution of the main groups, but, as will be seen, was published before some of the seats were finally allotted:- "The composition of the Cortes is now known, with the exception of 20 seats for which a second ballot will be held on Sunday in four provinces. The figures are:- LEFT COALITION - Socialists, 85; Izquierda Republicana, 75; Union Republica, 32; Esquerra, 20; Communists, 14; other left groups, 30. TOTAL, 256. RIGHT PARTIES - C.E.D.A., 94; Agrarians, 12; Monarchists, 12; Independents, 11; Traditionalists,11; other, 3. T0TAL, 143. CENTRE PARTIES. Portelists, 19; Lliga, 11; Radicals, 8; Progressists, 6; Others, 11. TOTAL, 55. The Left Coalition is therefore assured of an absolute majority in the new Cortes, for which 237 votes are necessary." 292/946/15b/39